The Effect Of Adding Flour Slurry (Umak) From Mocaf Flour To Pempek Dough On Consumer Acceptance - Rina Febriana,; Deckry Ganoma,; Nur Riska, (Jurnal Sains Boga, 2022)
Abstract Purpose of this study was to analyze the effect of adding flour slurry (umak) from mocaf flour to pempek dough on consumer acceptance on aspects of taste, aroma, and texture. The research was conducted at the Food Processing Laboratory of the Catering Education Study Program, Faculty of Engineering, State University of Jakarta from October 2020 to January 2022. This research used an experimental method and was supported by a literature study method. The experimental method was carried out to obtain the pempek formula using flour slurry (umak) with mocaf flour. Furthermore, the formula was tested to the general public using the preference test, to determine the panelists' likes and dislikes of pempek products with the addition of flour slurry (umak) from mocaf flour. Based on the results of Friedman it was concluded that there was an effect of adding mocaf flour slurry to aspects of taste, aroma and texture in pempek.test calculation Tuckey on the taste and texture aspects show that the pempek formula with the addition of 10% mocaf flour slurry and 15% is the most preferred product by consumers. Keywords: Flour slurry (Umak), Pempek, Mocaf, Consumer Acceptance